Multiple risk behaviors for non-communicable diseases and associated factors in adolescents - Melo RODRIGUES, Paulo Rogério (2023)
ObjectiveTo estimate the prevalence of risk behaviors for non-communicable diseases and analyze their associated factors in adolescents. MethodsA school-based cross-sectional study was conducted in 2008 with 1,139 adolescents aged 14 to 19 years attending public and private high schools in Cuiabá, Midwestern Brazil. Data were collected using a selfadministered questionnaire, including a semiquantitative Food Frequency Questionnaire. The prevalence of tobacco smoking, alcohol experimentation, physical inactivity, unsatisfactory meal pattern, and excessive intake of saturated fat and sodium were evaluated. The associations between risk behaviors and socioeconomic variables, weight status, and self-perceived health status were evaluated.Objective To estimate the prevalence of risk behaviors for non-communicable diseases and analyze their associated factors in adolescents. MethodsA school-based cross-sectional study was conducted in 2008 with 1,139 adolescents aged 14 to 19 years attending public and private high schools in Cuiabá, Midwestern Brazil. Data were collected using a selfadministered questionnaire, including a  emiquantitative Food Frequency Questionnaire. The prevalence of tobacco smoking, alcohol experimentation, physical inactivity, unsatisfactory meal pattern, and excessive intake of saturated fat and sodium were evaluated. The associations between risk behaviors and socioeconomic variables, weight status, and self-perceived health status were evaluated. ResultsThe most common risk behaviors were excessive sodium intake (88%), unsatisfactory meal pattern (72%), excessive intake of saturated fat (39%), and alcohol experimentation (39%). Four of 10 adolescents were exposed to two risk behaviors simultaneously. Among male adolescents, the main factors associated with risk behaviors were: type of school, class schedule, education level of the household head, weight status, and self-perceived health status. Among female adolescents, age, type of school, class schedule, and education level of the household head were the main factors associated with risk behaviors. ConclusionThe prevalence of exposure to risk behaviors for non-communicable diseases was high, highlighting the simultaneous presence of tobacco smoking and experimentation of alcoholic beverages. Special attention should be given to educational activities to minimize the effects of the simultaneous occurrence of multiple risk behaviors.